26. A randomized controlled cross-over double blind study protocol on THC/CBD oromucosal spray as an add-on therapy for post-stroke spasticity. Issue 12 (December 2017) - Marinelli, L.; Balestrino, M.; Mori, L.; Puce, L.; Rosa, G.; Giorello, L.; Currà, A.; Fattapposta, F.; Serrati, C.; Gandolfo, C.; Abbruzzese, G.; Trompetto, C.
Abstract : Understand if cannabinoids (THC:CBD) are useful in reducing post-stroke spasticity using a neurophysiological quantitative measure as primary endpoint. We will recruit 50 patients with spasticity following stroke to take THC:CBD in a double blind placebo-controlled crossover study. Spasticity will be assessed with a numeric rating scale for spasticity, the modified Ashworth scale and with the electromyographic recording of the stretch reflex. The cardiovascular risk will be assessed prior to inclusion. Blood pressure, heart rate, number of daily spasms, bladder function, sleep disruption and adverse events will be monitored throughout the study. A mixed-model ANOVA will be used to compare the stretch reflex amplitude between the time points; semi-quantitative measures will be compared using the Mann-Whitney test (THC:CBD vs placebo) and Wilcoxon test (baseline vs treatment). The study was registered on the EudraCT database with number 2016-001034-10 and approved by both the Italian Medicines Agency (AIFA) and local Ethics Committee. Data will be made anonymous and uploaded to an open access repository. Results will be disseminated by presentations at national and international conferences and by publication in journals of clinical neuroscience and neurology.